An Exploration of Usefulness of Instructional Learning Methods in Career Selection of Veterinary Graduates - Channappagouda, B and Sharma, G. R. K, (Indian Journal of Extension Education, 2016)
The veterinary education in India is facing a paradigm shift which calls for greater emphasis on competency and skillbased education. Veterinary Council of India (VCI) is working to address the issues by involving the various stakeholders.However still more in-depth appraisal of students' perceptions on various aspects of curriculum has not been performedempirically. In this background an attempt has been made to know the graduates overall perception about the differentinnovative instructional learning methods under VCI-2008 curriculum and their usefulness in career selection. For thispurpose, 150 post graduate students were randomly selected from five postgraduate teaching campuses of five southIndian veterinary universities to obtain the information through pre-structured schedule. The study revealed that studycircle and tracking courses were found not useful (48.0 per cent and 52.7 per cent respectively) while internship andentrepreneurial training activities were perceived as most useful (71.3 %) and useful (36.7 %) respectively. Further, morethan half perceived that clinical (diagnostic) exposure and extension activities as most useful (50.7 % and 61.3 %). Theresults indicate that much needed emphasis on practical problem solving skills with multidisciplinary approach in theundergraduate curriculum for effective career decisions by graduates.